2017
DOI: 10.1136/bjsports-2017-097891
|View full text |Cite
|
Sign up to set email alerts
|

Which exercise prescriptions improve quality of life and physical function in patients with cancer during and following treatment? A systematic review and meta-analysis of randomised controlled trials

Abstract: Exercise interventions, especially when supervised, have statistically significant and small clinical benefit on self-reported QoL and PF in patients with cancer. Unsupervised exercise intervention effects on PF were larger when prescribed at a higher weekly energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
138
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(155 citation statements)
references
References 111 publications
10
138
5
2
Order By: Relevance
“…Other studies supported that treatment status (Chiu et al, 2015;Hilfiker et al, 2018;Sweegers et al, 2018), aerobic and strength exercises could influence cancer patients' sleep (Chiu et al, 2015;Hilfiker et al, 2018;Kovacevic, Mavros, Heisz, & Fiatarone Singh, 2018;Mercier et al, 2017).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies supported that treatment status (Chiu et al, 2015;Hilfiker et al, 2018;Sweegers et al, 2018), aerobic and strength exercises could influence cancer patients' sleep (Chiu et al, 2015;Hilfiker et al, 2018;Kovacevic, Mavros, Heisz, & Fiatarone Singh, 2018;Mercier et al, 2017).…”
mentioning
confidence: 93%
“…Moreover, exercise intervention with supervised exercise or home-based exercise (Hageman, Fokkenrood, Gommans, Houten, & Teijink, 2018) and those with different exercise durations (Sweegers et al, 2018) have been reported positive effect on quality of life.…”
mentioning
confidence: 99%
“…Regular daily physical activity is associated with a reduced risk of cancer development and a reduction in mortality after the diagnosis of cancer [1][2][3]. Additionally, physical activity and exercise interventions have significant beneficial effects on the level of fatigue and quality of life in patients with cancer [4][5][6]. Previous studies have also shown that the magnitude of these beneficial effects is greater in patients with worse baseline values of physical activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, seria interessante analisar se o nível de condição física é um potencial mecanismo da relação AF-QV. Os programas de exercício acompanhados têm melhores resultados 50 , por isso os estudos de teor interventivo devem ser realizados em centros de EF, supervisionados por fisiologistas do exercício, de forma a reduzir o risco dos participantes não realizarem o que lhes foi solicitado e aumentar os níveis de segurança e eficácia e além disso devem ser aplicados diferentes planos de treino e diferentes tipos de treino, por exemplo, analisar os efeitos do treino com resistências ou o treino concorrente (aeróbio e de força), de forma a que se possa, aos poucos, ir compreendendo qual a frequência indicada, com que intensidade, durante quanto tempo, qual tipo, volume e periodização mais adequados. Seria interessante, no caso de sobreviventes sedentários, utilizar-se a abordagem da entrevista motivacional antes da prática de exercício, pois uma mensagem apropriada pode ter um papel importante ao nível da motivação para a prática de AF 51 e essa motivação pode ser essencial no que toca à adesão.…”
Section: Fracaunclassified